Deformations’ predictions by utilizing load blast enhanced against structural arbitrary langrangian eulerian methodologies : an LS-DYNA numerical simulation study - Mohd Zaid Othman,; Tan, Kean Sheng; Jestin Jelani,; Khairul Hasni Kamarudin,; Amir Radzi Ab Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Numerical simulation study to predict the transient (maximum) deformation of a rolled homogeneous armor plate which was loaded by the explosion of spherical trinitrotoluene bomb by using the ‘load blast enhanced’ and ‘structured arbitrary langragian eulerian’ methodologies in LS-DYNA is reported in this paper. Three numerical simulation models that utilized the ‘load blast enhanced’ and three numerical simulation models that utilized the ‘structured arbitrary langragian eulerian’ methodologies in LS-DYNA were produced and their results were used to predict and validate the deformations of three blast experimental tests of rolled homogeneous armor plates obtained from a published paper. This study showed that the numerical simulation results from the ‘load blast enhanced’ methodology gave better agreement than the ‘structured arbitrary langragian eulerian’ methodology with an average percentage differences of around 17% for all three cases.